“No Need to Dress to Impress” evidence on teleworking during and after the pandemic: A systematic review - Almeida, F.; Rodrigues, H.; Freitas, P. (Administrative Sciences, 2024)
Due to the working conditions imposed by the COVID-19 pandemic, teleworking also known as remote work has witnessed an increase in use, prompting a resurgence of interest in the topic among researchers. This article analyzes the evolution of literature before, during, and after the pandemic, as well as the research foci through an application of the antecedents, decisions, and outcomes framework. A systematic literature review methodology was employed using the evidence from 136 articles from 2016 to 2023. This review is about ‘telework literature in business, management, and accounting areas published in English’. Opportunities are identified for future studies and the findings afford managers with the advantage of understanding the crucial dimensions of telework. The bibliometric analysis revealed the significant impact of the COVID-19 pandemic on the widespread acceptance of teleworking globally, accompanied by a surge in studies on this subject. Additionally, the study provides deeper insights into the progression of teleworking literature since 2016 and organizes the various topics explored in this field.